Absolute leukocytes count and NLR as a diagnostic and prognostic biomarkers for severity of COVID-19 infection - Mohamedahmed, Khalid Abdelsamea; Abakar, Adam Dawoud (Jurnal Teknologi Laboratorium, 2021)
The current COVID-19 pandemic challenges not only the lack of awareness of the disease, but also the rapid diagnosis, the prediction of severe early disease, the clinical characterization of mortality and severity of patients, and the effective management that affects the global scale, resulting in low capacities of healthcare systems, the resilience of systems and global economics. Therefore, early differential diagnosis and prediction of SARS-COV-2 infection severity are needed. CRP and NLR are diagnostic markers commonly used, most available, effective, and economically used primarily to evaluate the ongoing systemic inflammatory response.